Agency risk control through reprisal - Lu, Qing; Hwang, Peter; Wang, Clement K. (Journal of Business Venturing, 2006)
We study agency risk control by venture capital (VC) firms to highlight the importance of VC reprisal ability. The central thesis of this paper is that a VC firm's due diligence effort as an ex ante screening for agency risk is contingent upon its ex post reprisal ability. Applying to the context of emerging markets, we develop a testable hypothesis and empirically test it using data from Singapore market. It is found that foreign VC firms that are relatively weak in reprisal ability spend more effort in due diligence screening compared to local VC firms.